Respon dan Aktivitas Peserta Didik dengan Menggunakan Model Pembelajaran Make A Match pada Pelajaran Pendidikan Agama Katolik - Oktavianey G.P.H Meman (Journal on Education, 2023)
This study aims to find out how students respond during learning with models make a match, and how are the activities of students and teachers in Catholic Religious Education lessons. The type of approach used is the Classroom Action Research (CAR) method. The results of the analysis found that at the beginning of the use of the learning model make a matchstudents are still confused and do not dare to present their cards. However, after the meetings in cycles 1 and 2, the responses of the students seemed very enthusiastic about the way the material was presented in this model and the learning activities had increased. As well as the results of student activities and teacher activities look significant in the observation table. Based on the findings above, it can be concluded that the learning modelmake a match influenced the responses and activities of students and teachers in Catholic Religious Education lessons at SMP Negeri 3 Bonti, Sanggau Regency.